PENGARUH PENERAPAN STRATEGI THINK PAIR SQUARE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 17 PADANG - Winda, Elvica Elva; Rahmi, Rahmi; K, Delsi. (STKIP PGRI Sumbar, 2013)
The background of this understanding mathematical concept still a lower class the learning prosess in centered on the teachers and discussion method dont to give satisfying achievement. This study aims to determine whether studentâs understanding of mathematical concept by applying methods of Think Pair Square is better that studentâs understandingÂ learning prosses conventional of class VIII SMPN 17 Padang regency in 2012/2013. This type of research is the design of experimental, with the population of this research is studentâs in class VIII SMPN 17 Padang that consist of all class. Sample of this research is studentâs in class VIII.8 that has been chosen as experimental and the class VIII.9 control class. The instrument that is used in the research is final test in the from of essays. Technique of data analysis is using one side t-test based on the result of data analysis, on average class experimental is 75, 85 and control class is 61, 59. Hypothesis test is gotten that P-value 0, 000 is smaller that Î± = 0, 05, because P-value < Î±, with reliability of the test is 0, 7611, so to push H0 and to receive H1. It can be concluded that the studentâs comprehension of mathematical concepts with the application strategy of Think Pair Square is better that studentâs understanding learning prosses conventional credibility level 95%.